PENGARUH PROGRAM LITERASI BACA TULIS TERHADAP MINAT BACA SISWA KELAS V SD 111 LEMBANG GOGOSO - Azrina Yahya, Nurul; Jamaluddin; Hasmiati (PENDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The influence of the reading and writing literacy program on reading interenst in class V student of SD Negeri 111 lembang gogoso, thesis. Madrasah ibtidaiyah teacher education study program, faculty of tarbiyah and teacher training ahmad dahlan sinjai university, 2023.This research aims to prove the effect of the reading and writing literacy program on the reading interest of fifth grade student at SD Negeri 111 Lembang gogoso. The type of research used in this research is expost facto research using aquantitative approach. The population in this study where fifth grade students at SD Negeri 111 Lembang gogoso with sampling using a saturated sampling technique with a total of 22 respondent.the data collection techniques used ar questionnaires and documentation as well as analysis using linearity analysis. Based on research conducted by researchers regarding the influence of the reading and writing literacy program on the reading interest of fifth grade students at SD Negeri 111 Lembang Gogoso, with a significance value of 0.153 > 0.05 or in other words a linearity test that there is a linear relationship between the variable X (literacy program) with variabel Y (reading interest). So it can be concluded that the reading and writing literacy program has an influence on the readuing interest of class V student at SD Negeri 111 lembang gogoso